PENGARUH KEPEMIMPINAN DAN KOMPETENSI KERJA TERHADAP KINERJA ANGGOTA DPRD KOTA SERANG - Nuraeni (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
Leadership is an effort to influence individuals, employees, workers, or subordinates, through or through communication to be able to achieve one or more goals. Work competence of a person who has the ability that has become part of him in his career. The performance of DPRD members is a measure of the output or work results compared to work inputs. The research objectives are as follows: To find out whether together there is an influence of leadership and work competence on the performance of DPRD members in Serang City.The sampling technique used in this study is the total sample or census technique. All members of the DPRD Serang City employees are the population and are used as the overall sample.The results showed that partially and simultaneously there was a positive and significant influence between Leadership and Work Competence on the Performance of Serang City DPRD Members.